Formal Constitutional Review Paradox: The Law on Legislation Making between Legal Procedure and Constitutional Norms - Ali, Chaidir; Fatmawati (As-Siyasi: Journal of Constitutional Law, 2025)
This paper analyses the paradoxical status of the Law on Legislation Making (LOLM) as a benchmark in formal constitutional review of legislation in Indonesia. Although the 1945 Constitution mandates procedural regulation through Article 22A, it offers minimal substance on the formal techniques of law-making, delegating this authority to statutory legislation. This gap creates ambiguity in judicial practice, especially for the Constitutional Court in performing formal reviews. Employing normative legal research, this study combines statutory, case, and comparative approaches, and also by examining 67 Constitutional Court decisions from 2003–2024. The findings revealed that LOLM is increasingly used as an imperative benchmark in formal reviews, despite some judicial reluctance and interpretive contradictions. The paper highlights three key jurisprudential provide within Constitutional Court Decision No. 001-021-022/PUU-I/2003, No. 27/PUU-VII/2009, and No. 91/PUU-XVIII/2020—which affirm LOLM’s normative authority in ensuring procedural compliance with the 1945 Constitution. Comparisons with constitutional practices in Jordan, Azerbaijan, Korea, Myanmar, and Türkiye show that legislative instruments is a legitimate judicial tool when constitutions are substantively incomplete. The research concludes that LOLM, although a statutory law, must be treated as a constitutionally imperative norm in formal judicial review. To preserve its legitimacy and legal stability, LOLM should regulate all technical aspects of legislative procedure comprehensively without sub-delegation to institutional regulations. LOLM must maintain fidelity to the 1945 Constitution principles while ensuring procedural rigor in legislative formation.